QAR : A Reading Strategy To Enhance Non-English Department Students Reading Skill - Tri Wahyuni; Nurlailalatulaqromi Nurlailalatulaqromi; Tiara Retno Haryani (Universitas Islam Lamongan, 2017)
Question Answer Relationship (QAR) strategy is a teaching strategy in teaching reading comprehension. By applying the strategy, teacher can assist the students to comprehend a reading text easier though they have a limit vocabulary. This strategy allows students to comprehend the text by relating the questions and the answers that can be classified into two big categories, in the text” and “in my head. At the end of the teaching learning process, students are supposed to be creative in comprehending a text using the QAR strategy. By implementing the strategy, the students are expected to extend the reading materials and continue to read more written materialsKeywords: Question Answer Relationship (QAR), Reading Skill